Constitutionalization of extractivism. Legal sensitivities around the constitutional reform process of the province of Jujuy, year 2023. (Papeles, 2025)
Constitutional reforms in Argentina tend to respond to short-term political interests, especially those linked to the incorporation of re-election clauses for executive powers (Altavilla, 2017). However, they have also included broader debates driven by various social sectors (Vitta, 2021, 2022). This article analyses Jujuy's partial constitutional reform in 2023, exploring its motivations from the perceptions of indigenous communities from the Third Malón de la Paz. Drawing on the legal sensibilities approach of Geertz (1994) and Godoy (2016), it examines how this reform consolidated public policies oriented towards economic development, constitutionalising an extractivist model. It incorporated regulations on climate change, energy transition, indigenous peoples and rural lands, which legitimise and consolidate this model. The research combines participant observation, semi-structured interviews and documentary analysis to address the process of constitutionalisation of extractivism in Jujuy.
Keywords: Constitutionalization; Extractivism; Constitutional reform; Jujuy; Legal sensitivities